PENGARUH INCOME, DEBT, FINANCIAL STRAIN, FINANCIAL ATTITUDE, DAN FINANCIAL LITERACY DENGAN FINANCIAL MANAGEMENT BEHAVIOR SEBAGAI VARIABEL MEDIASI TERHADAP FINANCIAL SATISFACTION PENGGUNA FINTECH LENDING DI SURABAYA - Safa Tasya Amalia; Nadia Asandimitra (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study investigates the financial satisfaction of fintech lending users. It also considers income, debt, financial strain, financial attitude, and financial literacy on financial management behaviour as a mediator. This study is a sort of conclusive causal research that uses quantitative research data. The techniques used in this study are purposive sampling. Data is collected through online questionnaires. The samples size for this study was 230 respondents that fit the criteria. The Structural Equation Model technique with AMOS tools was used to analyse the data in this study. This study shows that financial satisfaction is unaffected by income because the increase in revenue will increase lifestyle and financial responsibilities. Financial satisfaction is unaffected by debt because most respondents feel that they can fulfil their needs and lifestyle by debt. Financial satisfaction is unaffected by financial strain because most respondents are between 15-24, so they did not feel how financial stress is. Financial satisfaction is unaffected by financial attitude because most respondents cannot manage their finances. Financial literacy and financial management behaviour affect financial satisfaction. Financial management behaviour is unaffected by financial attitude because most respondents put their needs and lifestyle first. Financial literacy affects financial management behaviour. Financial management behaviour does not mediate financial attitude towards financial satisfaction. Financial management behaviour mediates financial literacy towards financial satisfaction. This research contributes to the thoughts of fintech lending users to understand financial concepts and avoid financial dissatisfaction.